REPRESENTASI PEREMPUAN INDONESIA ERA 70-AN DALAM SAMPUL MAJALAH FEMINA - Nadia Muty Ismalia; Kharisma Nasionalita (Prodi Ilmu Komunikasi FISIP Universitas Langlangbuana, 2017)
This study aims to determine the Semiotic meaning about “The Representation of Indonesian Women in the 70s through Femina Magazine’s Cover (Semiotic Analysis of Femina Magazine Cover’s first edition, September 18th 1972)” that analyzes the denotative, connotative and myth meanings according to Roland Barthes through symbols (Properties, Expressions, and Gestures), Typography, and Colors. The theories that analyzer used are Roland Barthes’ Semiotics theory with signification steps. The method that is used is a qualitative method with critic as its paradigm. The result of this research shows from the determination meanings through Roland Barthes’ denotative, connotative, and myth meanings on Femina’s first edition cover magazine, Indonesian Women in the 70s are represented as women who had multijobs, and responsibilities in multiple fields, not only internal fields but also external fields which at the same time Indonesian Women in the 70s are “maintained” by Women’s organizations running in the name of women.